Point of View (CCSS RL. 5.6). - Educational, Lorenz (Common Core State Standards., 2014)
Fill in the gaps of your Common Core curriculum! Each ePacket has reproducible worksheets with questions, problems, or activities that correspond to the packet's Common Core standard. Download and print the worksheets for your students to complete. Then, use the answer key at the end of the document to evaluate their progress. Look at the product code on each worksheet to discover which of our many books it came from and build your teaching library! This ePacket has 8 activities that you can use to reinforce the standard CCSS RL. 5.6: Point of View. -- Provided by publisher.